Extensive metastases in prostatic carcinoma with normal prostate-specific antigen and raised carcinoembryonic antigen – Small cell carcinoma of prostate: A rare entity - Sanjay Mhalasakant Khaladkar; Kunaal Mahesh Jain; Arijit Ghosh; Rajesh Kuber (Indian Journal of Medical and Paediatric Oncology)
Small cell carcinoma of prostate is a neuroendocrine tumor of prostate seen in 0.5%–2% of men with carcinoma prostate. Prostate-specific antigen (PSA) is a common tumor marker which is often raised in prostatic carcinoma. However, prostatic carcinoma can progress with normal or low serum PSA levels at the time of diagnosis. Carcinoembryonic antigen (CEA) is a tumor marker of different carcinomas. Small cell carcinoma prostate is a highly aggressive tumor which can progress with normal or low serum PSA levels and raised CEA levels. We report a case of 65-year-old male with enlarged prostate with extra-prostatic spread, hepatic metastases, metastatic retroperitoneal and pelvic lymph nodes, osteoblastic metastasis in lumbar spine with normal serum PSA, and raised CEA levels. Prostatic biopsy was suggestive of small cell carcinoma.